2018
DOI: 10.1016/j.intell.2018.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Intelligence in youth and health behaviours in middle age

Abstract: ObjectiveWe investigated the association between intelligence in youth and a range of health-related behaviours in middle age.MethodParticipants were the 5347 men and women who responded to the National Longitudinal Survey of Youth 1979 (NLSY-79) 2012 survey. IQ was recorded with the Armed Forces Qualification Test (AFQT) when participants were aged 15 to 23 years of age. Self-reports on exercise (moderate activity, vigorous activity, and strength training), dietary, smoking, drinking, and oral health behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
38
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 63 publications
3
38
0
3
Order By: Relevance
“…Additionally, higher childhood intelligence (as defined by age 11 IQ) is associated with a lower risk of mortality across the life course [16][17][18]. Furthermore, childhood intelligence associates with a healthier lifestyle and less morbidity in middle age, as well as a lower allostatic load in older age [19][20][21]. Furthermore, intelligence in early life is related to variability in cortical thickness, white matter macro-and micro-structure, as well as cognitive ability, fewer vascular lesions and lower risk of stroke in later life [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, higher childhood intelligence (as defined by age 11 IQ) is associated with a lower risk of mortality across the life course [16][17][18]. Furthermore, childhood intelligence associates with a healthier lifestyle and less morbidity in middle age, as well as a lower allostatic load in older age [19][20][21]. Furthermore, intelligence in early life is related to variability in cortical thickness, white matter macro-and micro-structure, as well as cognitive ability, fewer vascular lesions and lower risk of stroke in later life [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…For example, an investigation of the association of IQ measured in adolescence with self‐reported health by age 40 in a large US cohort study found that higher cognitive scores predicted better general and mental health, along with lower odds of having a number of conditions, including self‐reported “severe tooth or gum trouble” . Other work with that same cohort has highlighted an important role for intelligence in health behaviours known to be important for oral health, with, for example, better cognitive performance at ages 15‐23 years predicting higher rates of dental floss use and lower rates of smoking and consumption of sugary drinks in middle age . Data from a British cohort study showed that more intelligent children grow up to exercise more and eat more healthily as adults .…”
Section: Introductionmentioning
confidence: 99%
“…10 Other work with that same cohort has highlighted an important role for intelligence in health behaviours known to be important for oral health, with, for example, better cognitive performance at ages 15-23 years predicting higher rates of dental floss use and lower rates of smoking and consumption of sugary drinks in middle age. 11 Data from a British cohort study showed that more intelligent children grow up to exercise more and eat more healthily as adults. 12 Given the key role of sugars exposure in dental caries occurrence, 13 these findings suggest that intelligence might be a key determinant of oral health through life.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with higher cognitive function tend to participant more in health promoting behaviours. [11][12][13][14] Vascular risk factors, including diabetes and hypertension, have been associated with poorer cognitive function and greater cognitive decline. [15][16][17][18] Cognitive function, measured early in life, has been found to predict later life physical functioning and health status, 19 psychological distress, 20 psychiatric illness, [21][22][23][24][25] dementia, 26 and death.…”
Section: Introductionmentioning
confidence: 99%